Cerebellar hemorrhagic infarction after pterional craniotomy: Analysis of pathogenetical mechanisms - (:unkn) unknown (My University, 2003)
Objectives: Cerebellar venous infarction after supratentorial craniotomy has emerged as an infrequent, however, important and preventable problem in the recent literature. Cerebellar hemorrhage is secondary to venous infarction, however, exact pathogenetical mechanisms have not been demonstrated. In this study we evaluate possible etiological factors in 5 cases of cerebellar infarction and discuss them in the light of the recent literature. Methods: This is a retrospective series analysis of 5 cases of cerebellar infarction. For each case several preoperative factors, treatment methods and outcomes were evaluated and discussed. Results: No etiological factors common to all cases were found in our analysis except for the type of craniotomy and use of postoperative drains. However, no causative relationship could be established for either of these. For pterional craniotomy patients positioning and excessive CSF drainage may be suspected. Early and late outcome after treatment was good for all cases. Two cases required surgical treatment for cerebellar hemorrhagic infarction and related complications. Conclusions: Peroperative and postoperative excessive cerebrospinal fluid drainage and the position of the patient leading to hyperextension of the neck during surgery are the most important factors in the etiology.
Keywords: Cerebellum; Complication; Hemorrhagic infarction; Supratentorial craniotomy